Willingness to pay for use of water source for domestic consumption in Rangomali Village, Wolo District, Kolaka District - Alfarabi, Muh.; Razak, Rahman; Sabir (Economics and Business Journal (ECBIS), 2023)
Water is a very important natural resource for help to survive. Water perpendicularoma on providing has impacts. Unwise overuse of water resources you are horrified can jeopardize their sustainability. The objective of this study is to estimate the economic value of spring water utilization in Rangomari village. The method used is Willingness to Pay (WTP) Analysis using Conditional Valuation Method (CVM). As a result, the average I WTP is IDR 5,788.46 per month and the total IWTP is IDR 5,788.46 per month. 1,724,961.54 per month. The annual economic value of this urinary tract in Rangomali village is IDR 20,699,538.5. Governments are expected to implement payment of environmental services for water use and modernization of source management.